Religious Involvement and Suicidal Behavior among African Americans and Black Caribbeans - Taylor, Robert Joseph (2011)
This study explores the relationship between religious denomination, four dimensions of religious involvement, and suicidality (lifetime prevalence of suicide ideation and attempts) within a nationally representative sample of African American and Black Caribbean adults. The relationship between religious involvement and suicide for African Americans and Black Caribbeans indicated both similarities and differences. For both groups, religious involvement was largely protective of suicidal ideation and attempts, although, in some instances, specific measures were associated with higher suicidality. Looking to God for strength, comfort and guidance was protective against suicidal attempts and ideation, whereas stating that prayer is important in stressful situations was associated with higher levels of ideation for both groups and higher attempts among Black Caribbeans. For African Americans, reading religious materials was positively associated with suicidal ideation. Among Black Caribbeans, subjective religiosity was negatively associated with ideation and being Catholic was inversely associated with attempts while being Pentecostal was inversely associated with ideation. These findings are discussed in relation to previous research and current conceptual frameworks that specify multiple (e.g., prevention, resource mobilization) and often divergent pathways of religious effects on physical and mental health outcomes.